Hubungan Pola Asuh Orang Tua Terhadap Tumbuh Kembang Anak Usia 12-36 Bulan - Izdihar Hafizhah Az-Zahra; Najamuddin Najamuddin; Utami Murti Pratiwi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Parenting in the family is an action taken by parents in the family, so that children who get positive parenting can avoid growth and development disorders. This study aims to determine the relationship of parenting patterns to the growth and development of children aged 12-36 months. This research was conducted at Batua Raya Health Center and Tamalanrea Jaya Health Center. The total sample was 172 people with purposive sampling technique. This research is a quantitative study with a cross sectional approach method. The results of this study showed that parents who had positive parenting patterns had good nutrition 71 people, positive parenting patterns had poor nutrition 24 people, negative parenting patterns had good nutrition 40 people, negative parenting patterns had poor nutrition 37 people, positive parenting patterns had appropriate child development 71 people, positive parenting patterns had poor child development 24 people, negative parenting patterns had appropriate child development 41 people and negative parenting patterns had poor child development 36 people. The data analysis used is chi square and the p value for growth is 0.002 and the p value for development is 0.003. This shows that there is a relationship between parenting patterns and the growth of children aged 12-36 months.